DArTSNP based genetic diversity analyses in cassava (Manihote esculenta [Cranz]) genotypes sourced from different regions revealed high level of diversity within population - Abadura, N.S.; Abebe, A.T.; Rabbi, I.Y.; Beyene, T.M.; Abtew, W.G. (2025)
Understanding the extent of genetic diversity is a pre-requisite in cassava breeding program due to its available broad genetic base of the crop and have great opportunity for its genetic improvement. This study was designed to assess the genetic diversity of 184 cassava germplasm sourced from International Institute of Tropical Agriculture (IITA) and previous collection of Jimma Agricultural Research Center (JARC) by using DArTSNPs markers. The data were subjected to imputation and filtering for minor allele frequency of 0.01, 0.95 major allele frequency using TASSEL and Beagle. The resultants 9,310 informative SNPs were retained and used to perform analysis of molecular variance (AMOVA), genetic diversity, population structure, and dissimilarity-based clustering of the tested cassava germplasm. The results of AMOVA revealed higher variation within (91.3%) than between (8.7%) the study populations. The high average PIC (0.44), expected heterozygosity (0.50), major allele (0.61) and minor allele (0.28) frequency showed the existence of high variation in the study populations. Population structure analysis grouped the panels into six structures with the existence of admixtures. Similarly, principal component analysis, factor analysis and cluster analysis apparently divided the panels into six clusters. Both the introduced and locally collected germplasm formed three clusters, each creating some mixes of genotypes, indicating that alleles sharing common ancestral background. The overall results, the studied genotypes showed significant variations, which can render opportunity for association mapping and technical conservation purposes.